PALAEOENVIRONMENTAL INTERPPRETATION OF THE LATE TRIASSIC FRAELE FORMATION (ORTLES NAPPE, AUSTROALPINE DOMAIN, LOMBARDY) (Rivista italiana di Paleontologia e Stratigrafia, 1997)
The Fraele Formation crops out in the Ortles Nappe (upper Valtellina, Northern Italy), structurally part of the Central Austroalpine Domain. It consists of fine siliciclastics alternating with carbonates, mostly limestones,rare dolostones and marls. The formation differs lithologically from the underlying Norian Dolomia del Cristallo because of different paleonvironmental evolution.The change in environmental parameters was controlled mainly by a climatic change to more humid conditions.This favoured on one hand the mobilisation and trasport by rivers of siliciclastic material from the continent to the Tethys gulf,and on the other influenced the sea-water chemistry.Freshwater influxes lowered salinity and inhibited early dolomitisation. Input of low density freshwater resulted in the astablishment of a permanent water mass stratification which influenced the benthic life. This paleoenvironmental reconstruction fits with the sudden clastic input which occurred in several palaeogeographic domains of the western Tethys realm (Austroalpine, Southalpine, Apennine, Hungary, Poland, Slovakia) during the Late Norian.